"Process-Space" Festival 1992 1993 1994 1995. - Grozdanov, Dimitar; Mussakova, Elissaveta; Ruenov, Ruen (Sofia : Soros Center for the Arts, 1996)
Lucanu, Doina ; Schmid, Jeanne ; Gattiker, Irene ; Graedel, Linda ; Nitsch, Michael ; Volkart, Peter ; Ivanova, Elena ; Panayotova, Elena ; Boyadjiev, Bojidar ; Tzankov, Dr. Nikolay ; Kasandjieva, Dr. Jeana ; Pavlov, Milko ; Kostov, Wentseslav ; Popov, Stephan ; Bistritchki, Ivo ; Yordanov, Danil ; Witchev, Anatoli ; Genova, Nadja ; Michaylova, Albena ; Miraztchiev, Emil ; Marinoff, Kerstin ; Russenov, Rumen Manolov & Dimitar ; Galabina, Lora & Christina ; Grozdanov, Dimitar
biografie
"Process-Space" Festival 1996, Sofia, 1996
Bulgaars & Duits
boek